Nature contact and health risk behaviours: Results from an 18 country study - Martin, L.; White, M. P.; Pahl, S.; May, J.; Newton, J. N.; Elliott, L. R.; Cirach, M.; Grellier, J.; Bratman, G. N.; Gascon, M.; Lima, M. L.; Nieuwenhuijsen, M.; et al. (Health and Place, 2025)
Emerging evidence suggests that residential greenspace is associated with a lower prevalence of health risk behaviours, but it remains unclear whether these effects are generalizable across countries or different types of nature contact. Using representative cross-sectional samples from 18 countries/regions, we examined the associations between two types of nature contact (greenspace, nature visits), current smoking and everyday drinking. After controlling for a range of covariates, greenspace was inversely associated with current smoking and everyday drinking. Visiting natural spaces at least once a week was linked to a lower prevalence of current smoking, but unrelated to everyday drinking. Increasing residential greenspace could be a promising strategy for reducing multiple health risk behaviours, whilst visit-based interventions may be a more appropriate target for smoking cessation.